Role of Radiotherapy in Metastatic Renal Cell Carcinomas: An Evolutionary Journey in a Misunderstood Histological Type - Chan Woo Wee; Jaeho Cho (Journal of Urologic Oncology)
Renal cell carcinoma (RCC) has traditionally been considered one of the most radioresistant tumors based on in vitro and clinical studies that utilized a low biologically effective dose. However, recent studies have suggested that administering a higher radiation dose to RCC can lead to satisfactory local control and potentially long-lasting disease control. Thanks to significant advances in radiotherapy technology, it is now feasible to deliver higher radiation doses to tumors while preserving the organs at risk. Furthermore, over the past decade, a crucial role of radiotherapy has emerged in metastatic cancers, both for symptom palliation and for the elimination of tumor niches. This review discusses the current evidence and future perspectives concerning the role of radiotherapy in metastatic RCC.